Bioaccumulation of organochlorine contaminants and ethoxyresorufin‐o‐deethylase activity in southern California round stingrays (Urobatis halleri) exposed to planar aromatic compounds. (June 2014) - Lyons, Kady; Lavado, Ramon; Schlenk, Daniel; Lowe, Christopher G.
Abstract While contaminant concentrations have been reported for elasmobranchs around the world, no studies have examined bioaccumulation patterns across male and female age classes. The round stingray (Urobatis halleri) is a local benthic species that forages near areas of high organochlorine contamination and represents a good elasmobranch model. Polychlorinated biphenyls (PCBs), DDT, and chlordanes were measured in juvenile and adult male and female stingrays from areas in southern California, USA (n = 208), and a nearby offshore island, Santa Catalina (n = 34). Both mainland juvenile male and female stingrays showed a significant dilution effect. After maturity, summed contaminant concentrations significantly increased with size for adult males (median 11.1 µg/g lipid wt) and females (5.2 µg/g lipid wt). However, the rate of bioaccumulation was substantially greater in male stingrays than in females, likely a result of the females' ability to offload contaminants to offspring during pregnancy. In addition, males and females showed significant differences in their contaminant profiles, suggesting differential habitat use. Male and female stingrays collected from Santa Catalina Island had significantly lower concentrations (0.51 µg/g and 0.66 µg/g lipid wt, respectively), approximately 5 times less than those of mainland animals. Potential toxicity effects mediated through activation of the aryl hydrocarbon receptor were explored through ethoxyresorufin‐O‐deethylase (EROD) activity assays. Mainland male stingrays exhibited significantly greater EROD activities than Catalina males (481 pmol/min/mg protein and 55 pmol/min/mg protein, respectively); however, activity levels in female stingrays from both locations were comparable (297 pmol/min/mg protein and 234 pmol/min/mg protein, respectively) and lower than those in mainland males. The results suggest that PCBs and/or other structurally related contaminants may be inducing a biological response in mainland males but not females, possibly the result of a dampening effect of estradiol; however, the exact physiological repercussions of exposure remain to be determined. Environ Toxicol Chem 2014;33:1380–1390. © 2014 SETAC